THE LEANNESS LEVEL OF THE FINANCIAL INSTITUTIONS IN CZECH REPUBLIC - Okpu Yo, Agbor Takang; Martínez, Felipe; Krejčová, Nikola, 1974-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2019)
This bachelor thesis focuses on the evaluation of the level of leanness of financial institutions in Czech Republic. This bachelor thesis follows the literature review of lean management with a focus on operations management of the financial sector. This research is carried out following the qualitative interview research strategy. The research questionnaire focuses on obtaining information on the performance of the operations of the financial institutions. The qualitative information obtained, reflects the efficiency of the operating systems and workplace environment of the financial institution. In addition, an analysis of the level of leanness of the operations of the financial institution. Furthermore, a consolidated evaluation of the financial information was conducted for the entire financial industry and a grading score to access the level of leanness of the financial institution in Czech Republic.
Vedoucí práce: Felipe Martínez
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: business administration/corporate finance and management [obor bakal. práce]; bakalářské práce; bachelor's theses